Manajemen Administrasi Majelis Taklim dan Zikir Darul Iman dalam Meningkatkan Efektivitas Kegiatan Dakwah - Lingghom Miranda Hanum Pakpahan; Fizria Suhada; Muhammad Ferdi; Alfin Alfarihin; Hendra Kurniawan (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
This study aims to determine and analyze the administrative management implemented at the Majelis Taklim and Zikir Darul Iman and its role in increasing the effectiveness of da'wah activities. The focus of this research includes planning, organizing, implementing, and supervising administration, as well as the extent to which this administrative system has been implemented and the obstacles encountered. This study used a qualitative approach with a descriptive approach. Data collection techniques included observation, interviews, and documentation of the administrators of Majelis Taklim and Zikir Darul Iman in several regions. The results indicate that Majelis Taklim and Zikir Darul Iman have implemented a fairly well organized and structured administrative management system, characterized by a clear division of administrative duties, routine activity scheduling, coordinated congregation data collection, and transparent financial management, although still carried out manually. The administrative system, which is not centralized by a single administrator, makes the implementation of da'wah activities more effective and sustainable. The main obstacle faced is limited funding for developing a more modern administrative system. Thus, good administrative management has proven to be a crucial factor in supporting the effectiveness of the Majelis Taklim and Zikir Darul Iman's da'wah activities.